2016
DOI: 10.1021/acsami.6b07419
|View full text |Cite
|
Sign up to set email alerts
|

Formation of He-Rich Layers Observed by Neutron Reflectometry in the He-Ion-Irradiated Cr/W Multilayers: Effects of Cr/W Interfaces on the He-Trapping Behavior

Abstract: Cr/W multilayer nanocomposites were presented in the paper as potential candidate materials for the plasma facing components in fusion reactors. We used neutron reflectometry to measure the depth profile of helium in the multienergy He ions irradiated [Cr/W (50 nm)]3 multilayers. Results showed that He-rich layers with low neutron scattering potential energy form at the Cr/W interfaces, which is in great agreement with previous modeling results of other multilayers. This phenomenon provided a strong evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…MoSe 2 nanodots were biocompatible in vitro at concentrations up to 160 µg mL −1 and exhibited better photostability than ICG. In vitro PTT [203] Copyright 2017, American Chemical Society. application of these MoSe 2 nanodots was demonstrated in HeLa cells incubated with 40 µg mL −1 MoSe 2 and treated with 2 W cm −2 , 785 nm light irradiation, displaying pronounced effect as cell viability of less than 8% was achieved.…”
Section: Photothermal Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…MoSe 2 nanodots were biocompatible in vitro at concentrations up to 160 µg mL −1 and exhibited better photostability than ICG. In vitro PTT [203] Copyright 2017, American Chemical Society. application of these MoSe 2 nanodots was demonstrated in HeLa cells incubated with 40 µg mL −1 MoSe 2 and treated with 2 W cm −2 , 785 nm light irradiation, displaying pronounced effect as cell viability of less than 8% was achieved.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…In a study by Chen et al, photother-mal application of MoS 2 nanosheets with degradable property was reported. [203] MoS 2 -PAA was synthesized by hydrothermal reaction of ammonium molybdate tetrahydrate and PAA, and subsequently functionalized with PEG-amine to produce MoS 2 -PPEG (Figure 21A). After 5 min of 1 W cm −2 808 nm light irradiation, temperature of 200 µg mL −1 MoS 2 -PPEG solution rose from 25.8 to 51.4°C.…”
Section: Photothermal Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…[34] They found that these LA-PEG-modified TMDC materials all exhibit desirable compatibility in a physiological environment with additional excellent biomedical applications, such as multimodal imaging and synergistic therapy for cancer treatment. In addition to PEG, other polymers such as poly(acrylic acid) (PAA), [143] polyethylenimine (PEI), [144] combined PAA-PEG [145] or PEI-PEG, [131,146] or polyaniline (PANI), [130] as well as generation-5 poly(amidoamine) dendrimers-lipoic acid (G5-LA) [147] are also widely used in the process for functionalization of TMDCs. For example, similar to LA-PEG functionalization, effective polymer conjugation via the disulfide bond was reported by Kim et al, in which MoS 2 was modified with LA-modified PEI, as well as thiolated PEG polymers (MoS 2 -PEI-PEG) (Figure 9a).…”
Section: Polymersmentioning
confidence: 99%